THE EFFECT OF TECHNICAL ASSET, FINANCIAL ASSET AND MACRO-ECONOMIC ON RETURN BITCOIN - Muhammad Rizky Nasution; Isfenti Sadalia; Nisrul Irawati (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This study uses research variables such as Trading Volume, Market Capitalization, S&P 500 Index, World Oil Price, Gold Price on Bitcoin Returns. The data source in this study is through internet media with the sites https://coinmarketcap.com/, https://finance.yahoo.com/, and other sites that support this research. The data used in this study are time series, and the target population for the data sample is 1,096 (3 years x 365) daily report data. The data were collected from January 1, 2020, to December 31, 2022, through the release of daily bitcoin transaction reports. Time series data analysis using Engel Granger's Error Correction Model is the method employed (ECM). The analysis tool used is the Econometric Views (Eviews) which is one of the computer econometric program. The results of this study where trading volume has a positive and insignificant effect on bitcoin returns. The impact of market capitalisation on bitcoin returns is both favorable and significant. Returns on bitcoin are positively and significantly impacted by S&P 500. The returns on bitcoin are negatively and insignificantly impacted by the price of world oil. Returns on bitcoin are positively and negligibly impacted by the gold price.